The Influence of Member Participation on Remaining Business Results in the Harapan Bersama West Pasaman Multi-Business Cooperative - Rahmanda, Rahmanda; Riadi, R. M.; Mujiono, Mujiono (CV. Rayyan Dwi Bharata, 2024)
This research aims to determine the influence of cooperative member participation on the remaining Hsaha proceeds from the Harapan Bersama West Pasaman multi-business cooperative. The method used in this research is a quantitative descriptive method. With a population of 210 students and a sample of 53 people in this research. The data collection instrument used in this research is a questionnaire in the form of a Google form which uses a Likert scale for the independent variable, namely Member Participation (X1). The analysis technique used is simple linear regression. The research results obtained show that Partial Member Participation has an effect on the Remaining Cooperative Business Results. This is based on the results of the analysis, the calculation shows the value of tcount ttable (2.5110.679). So it can be concluded that Member Participation influences the remaining Cooperative Business Results.